PERANAN SEJARAH HUKUM DALAM PEMBENTUKAN UNDANG-UNDANG DI INDONESIA - Rika Noviantini; Hidayati; Imas Naeni; Fuji Utomo; M Multazam; Iwahori Badia Y (PT. Hasba Edukasi Mandiri, 2025)
Legal history plays a fundamental role in shaping the character and direction of the Indonesian legal system. Through historical studies covering the pre-colonial, colonial, and modern periods, it becomes clear that the national legal system is a synthesis of customary law values, Islamic legal principles, and Dutch legal heritage, all of which have undergone processes of reform and reconstruction throughout the nation’s development. This study analyzes how these historical developments influence the formation of national legislation and how the integration of historical values can strengthen Indonesia’s legal identity amid the challenges of globalization and modernization. In addition, this study outlines methodological challenges, low historical awareness, and the influence of globalization, which often shifts local values within modern legislation. The study also highlights the prospects for developing a history-based national legal system through the strengthening of legal education, interdisciplinary research, and strategies for harmonizing customary, Islamic, and modern legal principles. Thus, integrating legal history into legislation is not only essential for maintaining identity continuity but also serves as a foundation for building an Indonesian legal system that is distinctive, just, and sustainable.